Sistem Bagi Hasil dan Tingkat Kepuasan Petani di Desa Sukamakmur Kecamatan Telukjambe Timur Kabupaten Karawang Jawa Barat - IKE IMADE BAYU KURNIAWATI; I MADE SARJANA; I GEDE SETIAWAN ADI PUTRA (Agribusiness Study Program, Faculty of Agriculture, Udayana University, 2022)
Revenue Sharing System and Farmer Satisfaction Level in Sukamakmur Village, East Telukjambe District, Karawang Regency, West Java Revenue sharing system is an agreement made between farmers and landowners or concerned. One of the villages that runs the revenue sharing system is Sukamakmur Village Java with an area of 2.81 km2. The purpose of this research is to know the revenue sharing system that is running and the satisfaction of farmers over the revenue sharing system run in Sukamakmur Village. The research was conducted qualitatively by collecting data through interviews, observations, and documentation. The result of the research is the revenue sharing system run in Sukamakmur Village is 1:1 revenue sharing with capital derived from farmers, revenue sharing is done when farmers have sold grain to middlemen. The rights and obligations that farmers have during the work of the land that is farmers must carry out their farming in the land in accordance with the type of crops that have been agreed and farmers can insure crops on the land to the chairman of the farmer group. Judging from the satisfaction of farmers regarding the revenue sharing system run by farmers are not satisfied with the condition of the cultivated land and cost effectiveness, and satified with the position of farmers as farmers, and the authority owned as farmers to the land. It can be concluded that farmers are less satisfied with the results received because sometimes it is not enough to pay for a living and return capital. The advice that can be given in this study is that farmers who make a written agreements, farmers using combine harvester machine, changing the revenue sharing or leasing land, using agricultural cooperatives, doaing rotation and security of agricultural land.